2020
DOI: 10.3389/fpsyt.2020.578264
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Influence of Depressive Symptoms Between Mothers and Fathers During the First Postpartum Year: A Comparison Among Full-Term, Very Low, and Extremely Low Birth Weight Infants

Abstract: Background: Perinatal depression (PND) in mothers and fathers of very low and extremely low birth weight (VLBW and ELBW) infants has not been studied extensively. In particular, no studies investigated the reciprocal influence of depressive symptoms during the first 12 months postpartum. This study aimed at exploring the impact of the severity of prematurity on maternal and paternal PND during the first postpartum year; specifically, we used an Actor–Partner Interdependence Model (APIM) to test the interdepend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 76 publications
1
17
1
Order By: Relevance
“…Moreover, contrary to the results of other authors (Neri et al, 2020;Thiel et al, 2020), we have not found a statistically significant correlation between maternal and paternal depressiveness scores. In addition, due to the low internal consistency of EPDS for the assessment of fathers at 6 months, these results could not be used in the analyses.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Moreover, contrary to the results of other authors (Neri et al, 2020;Thiel et al, 2020), we have not found a statistically significant correlation between maternal and paternal depressiveness scores. In addition, due to the low internal consistency of EPDS for the assessment of fathers at 6 months, these results could not be used in the analyses.…”
Section: Discussioncontrasting
confidence: 99%
“…This is especially relevant in light of recent findings on early programming of preterm infants' temperament, via gene methylation processes, due to neonatal exposure to pain and stress related to medical procedures and treatment in the Neonatal Intensive Care Unit (NICU) (Cassiano et al, 2016;Montirosso et al, 2016). Furthermore, interconnections between the severity of preterm infant medical conditions and parental mental health have already been established (Agostini et al, 2014;Carson et al, 2015;Neri et al, 2020). Neonatal data that we have collected and included in our sample characteristics clearly point to the numerous challenges that the infants under study were exposed to, not to mention an additional emotional burden for the parents.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations